How worker productivity and wages grow with tenure and experience: The firm perspective - Andrew Caplin; Minjoon Lee; Søren Leth-Petersen; Johan Sæverud; Matthew D. Shapiro (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
How worker productivity evolves with tenure and experience is central to economics, shaping, for example, life-cycle earnings and the losses from involuntary job separation. Yet, worker-level productivity is hard to identify from observational data. This paper introduces direct measurement of worker productivity in a firm survey designed to separate the role of on-the-job tenure from total experience in determining productivity growth. Several findings emerge concerning the initial period on the job. (1) On-the-job productivity growth exceeds wage growth, consistent with wages not being allocative period-by-period. (2) Previous experience is a substitute, but a far less than perfect one, for on-the-job tenure. (3) There is substantial heterogeneity across jobs in the extent to which previous experience substitutes for tenure. The survey makes use of administrative data to construct a representative sample of firms, check for selective non-response, validate survey measures with administrative measures, and calibrate parameters not measured in the survey.
Keywords: E24; J24; J30; 330; Productivity; Wages; Tenure; Experience; Firm survey